Denied the Right to Health Care: Regulatory Changes to Canada's Medical Inadmissibility Provision - Kariane (McMaster University Library Press, 2019)
In June 2018, Immigration, Refugees, and Citizenship Canada (IRCC) enacted changes to the medical inadmissibility provision (section 38(1)(c)) of the Immigration and Refugee Protection Act (IRPA) in the form of a temporary public policy. These consisted of raising the cost threshold for defining "excessive demand," and narrowing the scope of "social services" eligible to be deemed a burden to the state when considering temporary and permanent residency applications to Canada. Reasons cited for the proposed changes included promoting the inclusion of applicants with disabilities (such as children in need of special education) and of applicants requiring costly prescription drugs (such as HIV-positive individuals). Although impacts at this stage are preliminary, these amendments are expected to greatly decrease the number of medical inadmissibility findings issued to permanent and temporary residence applicants on a yearly basis. This reform occurred in the context of mounting societal and political pressures calling for a more humanitarian approach to immigration policy. It illustrates important tensions underlying the state's obligation to protect the collective good of society while navigating the ethical implications of exclusionary immigration measures.